Probing the Electronic Structures of BaTiO3/SrTiO3 Multilayered Film with Spatially Resolved Electron Energy-Loss Spectroscopy - Liu,G; Wang,Y; Zou,B; Liang,W; Alford,NM; McComb,DW; Petrov,PK (Journal of Physical Chemistry C, 2016)
A multilayered film of BaTiO3/SrTiO3 was grown on a LaAlO3 substrate using dual-target pulsed laser deposition technique. High-resolution scanning transmission electron microscopy observations show that the nine unit-cell BaTiO3 layer and the three unit-cell SrTiO3 layer are alternatively arranged in the epitaxial film where a sharp interface exists between the BaTiO3 and SrTiO3 layers. Electron energy-loss spectroscopy analysis demonstrates that the O-K edge spectra of SrTiO3 and BaTiO3 layers are quite distinct; in particular, the energy-loss peak at 547 eV in the SrTiO3 spectrum splits into two peaks in the BaTiO3 spectrum. The multiple-scattering calculations of O-K edge spectra for BaTiO3 and SrTiO3 agree well with the experimental results. The low-energy region (<542 eV) of the O-K edge spectra for both BaTiO3 and SrTiO3 is mainly caused by the hybridization of the O 2p with Ti 3d orbitals. The splitting peaks between 542 and 552 eV in the O-K edge spectra of BaTiO3 are attributed to its complex crystal structure including two unequal oxygen sites and low site symmetry.